Use low-carbon ingredients as guidelines for green cuisine menu development - Dr.ChienChung Yu, Chun Chu Liu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
With the rise of consumer awareness, food safety is important in the process of developing the tourism industry. Therefore, the development of green cuisine is an inevitable trend. Green cuisine plays an important role in green tourism. Therefore, we should make good use of local agricultural resources to promote Low-carbon food materials create substantial benefits for the green supply chain. Therefore, this study collected 12 expert opinions and constructed the key evaluation criteria for the development of green cuisine menu development. It is recommended to use local ingredients and green supply chains to develop marketing strategies for the main target source of customers.